Physiotherapy and Rehabilitation in a Child with Joubert Syndrome - Özge İpek; Özge Akyolcu; Banu Bayar (Case Reports in Pediatrics)
Objective. Joubert syndrome (JS) is a rare autosomal recessive genetic disorder characterized by brain malformation, hypotonia, breathing abnormalities, ataxia, oculomotor apraxia, and developmental delay. The purpose of this study was to report the efficiency of the physiotherapy and rehabilitation program in a child with JS. Materials and Methods. Our case is a 19-month-old female child with mild clinical signs of JS. The pretreatment and posttreatment motor functioning level of the case was evaluated through the Gross Motor Function Measure (GMFM), whereas the independence level was evaluated through the Pediatric Functional Independence Measure (WeeFIM). The case was included in the rehabilitation program by the physiotherapist for one hour for five days a week throughout the period of 13 months in accordance with the neurodevelopmental treatment principles. Results. The case was able to turn around from the supine position to the reverse direction by oneself, and she was able to rise on her forearms facedown and was able to sit, crawl, and walk independently. The GMFM score was 210, whereas WeeFIM score was 65. Discussion. In the direction of those findings, in Joubert Syndrome, physiotherapy and rehabilitation can be effective in coping with the symptoms causing developmental delay.